Crack-reduced alumina/aluminum titanate composites additive manufactured by laser powder bed fusion of black TiO2−x doped alumina granules. Issue 8 (July 2022) - Pfeiffer, Stefan; Florio, Kevin; Makowska, Malgorzata; Marone, Federica; Yüzbasi, Sena; Aneziris, Christos G.; Van Swygenhoven, Helena; Wegener, Konrad; Graule, Thomas
Abstract: Laser powder bed fusion is an emerging industrial technology, especially for metal and polymer applications. However, its implementation for oxide ceramics remains challenging due to low thermal shock resistance, weak densification and low light absorptance in the visible or near-infrared range. In this work, a solution to increase the powder absorptance and to reduce cracking during laser processing of alumina parts is given. This is achieved by the use of a homogeneously dispersed and reduced titanium oxide additive (TiO2−x ) within spray-dried alumina granules leading to formation of aluminum titanate with improved thermal shock behavior during powder bed fusion. The impact of different reduction temperatures on powder bed density, flowability, light absorption and grain growth of these granules is evaluated. Crack-reduced parts with a density of 96.5%, a compressive strength of 346.6 MPa and a Young's modulus of 90.2 GPa could be manufactured using powders containing 50 mol% (43.4 vol%) TiO2−x . Highlights: Laser processing of black titanium oxide (TiO2−x ) doped alumina granules. Improved powder absorptance by color change upon reduction under Ar/H2 atmosphere. Crack-reduced parts by the formation of aluminum titanate from Al2 O3 and TiO2−x . Crack reduction successful starting from a TiO2−x amount of 50 mol%. Highest achieved part density and compressive strength of 96.5% and 347 MPa.